Diagnostic Yield of Abdominal Wall Fat Pad Biopsy for Systemic Amyloidosis in a Low-Prevalence Referral Cohort - Teixeira, João; Teixeira, Diogo; Coelho, André; Cardoso, José Carlos (Dermatology Practical & Conceptual, 2026)
Introduction: Systemic amyloidosis is a rare disorder characterized by extracellular amyloid deposition in tissues, leading to variable organ dysfunction. Abdominal wall fat pad biopsy is widely used as a minimally invasive diagnostic approach, yet its sensitivity varies according to population and technique. Objectives: To assess the diagnostic yield and adequacy of abdominal wall fat pad biopsy for systemic amyloidosis in a low-prevalence referral cohort. Methods: A retrospective study was conducted at a tertiary university hospital including all consecutive abdominal wall fat pad biopsies performed between January 2021 and June 2025. Clinical data, histopathological findings, and biopsy techniques were reviewed. Adequacy was defined by the presence of well-preserved subcutaneous fat with vascular and stromal structures. Congo red–positive deposits showing apple-green birefringence confirmed amyloidosis. Results: A total of 106 biopsies from 103 patients (mean age 71.1 ± 12.2 years; 56.3% male) were analyzed. Clinical indications included MGUS (65.0%), multiple myeloma (27.2%), and suspected infiltrative cardiomyopathy or nephrotic proteinuria (8%). Overall, 7/106 biopsies (6.6%) were positive for amyloid. Sensitivity among patients with known systemic amyloidosis was 66.6% (6/9), and specificity was 100%. Only two of 94 patients (2.1%) without prior diagnosis were newly identified. Three punch biopsies (2.8%) were inadequate due to insufficient fat. Conclusions: Abdominal wall fat pad biopsy is safe and minimally invasive but demonstrates limited diagnostic yield in unselected low-risk populations. It should not be used as a screening tool in patients with monoclonal gammopathies without organ involvement. Adequate tissue sampling and careful patient selection are essential to optimize diagnostic performance.